2020
DOI: 10.1017/s0033291720002834
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of harm in mindfulness-based stress reduction

Abstract: Background Mindfulness meditation has become a common method for reducing stress, stress-related psychopathology and some physical symptoms. As mindfulness programs become ubiquitous, concerns have been raised about their unknown potential for harm. We estimate multiple indices of harm following Mindfulness-Based Stress Reduction (MBSR) on two primary outcomes: global psychological and physical symptoms. In secondary analyses, we estimate multiple indices of harm on anxiety and depressive symptoms, discom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…On the basis of those completing posttreatment measures, HMP appears safe in that the rates of clinically significant increases in distress were rare (3%) and were less common than the rates in the control condition (16%). This finding is consistent with a recent large-scale evaluation of the deterioration in MBSR [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of those completing posttreatment measures, HMP appears safe in that the rates of clinically significant increases in distress were rare (3%) and were less common than the rates in the control condition (16%). This finding is consistent with a recent large-scale evaluation of the deterioration in MBSR [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite a growing interest in this area, there has been no systematic review addressing potential AEs across the whole range of meditation reports. Two recent reviews have only included the literature on mindfulness-based interventions and found that these meditation interventions were no more likely to lead to harm than a wait-list control, or they identified an overall very low rate of adverse events (1% across 36 randomized controlled trials) (25,26). By contrast, the present study aims to review the wide literature on MAEs by including all types of empirical reports, regardless of their methodological approach.…”
Section: Introductionmentioning
confidence: 99%
“…Study side effects were not assessed, though harm is infrequent with guided mindfulness interventions. 29 The themes that emerged for ways of helping others may be specific to those practicing mindfulness (e.g., sharing mindfulness with others) and the recruitment strategies utilized (e.g., spiritual communities). Though participants reported helping behaviors during COVID-19, mindfulness’ effects on the desire to help others were not assessed.…”
Section: Discussionmentioning
confidence: 99%